A Fas associated factor negatively regulates anti-bacterial immunity by promoting Relish degradation in Bombyx mori. (August 2015) - Ma, Xiaojuan; Li, Xianyang; Dong, Shifeng; Xia, Qingyou; Wang, Fei
Abstract: Negative regulation is required to keep NF-κB-dependent immune response under tight control. In previous study, we have identified a Fas associated factor (FAF) family member in Bombyx mori, BmFAF, and proposed it may act as a negative regulator in immune response. In this study, we found knock-down of BmFAF by RNAi led to a remarkable increase in transcriptional level of several antimicrobial peptide genes, including BmCecropinA1 and BmMoricin, and higher survival rate to Gram-negative bacterial infection. We also confirmed the regulatory role of BmFAF in suppressing NF-κB-dependent transcription by employing an inducible promoter in BmE cells. Consistent with these physiological phenotypes, BmFAF suppressed the activity of the essential transcription factor, Relish, in IMD signaling pathway by promoting its proteasomal degradation through direct interaction. In addition, by constructing various truncation mutants, we further demonstrated that UBA domain in BmFAF is required for the inhibitory role, and potential ubiquitination also occurs in this domain. Taken together, our results suggest that BmFAF is a negative regulator of IMD pathway by mediating degradation of Relish. Graphical abstract: Highlights: BmFAF knockdown increases silkworm survival rate against Serratia marcescens infection and antimicrobial peptide expression. Cell-based assay confirms the regulatory role of BmFAF in suppressing the activity of Relish. BmFAF interacts with Relish and promotes its proteasomal degradation. UBA domain is required for the inhibitory role of BmFAF.